A preliminary assessment of the spatial and temporal patterns of sand and dust storms over the Sahara - Sahar A. Saleh; Saleh A․ S․; Hesham Badawy (Scientific African)
The Sahara Desert, the preeminent global producer of airborne dust, is crucial for comprehending the geographical and temporal dynamics of sand and dust storms (SDSs), especially as climate change and anthropogenic activities exacerbate desertification. This study offers a spatiotemporal analysis of SDSs in the Sahara from 2000 to 2020, incorporating 2196 daily satellite observations from NASA’s Giovanni and POWER platforms alongside GIS-based regional clustering. We evaluated changes in SDS frequency, intensity, duration, and distribution over the past two decades. This study identified primary dust source locations, such as the Bodélé Depression, Western Sahara, and Libyan-Algerian sand seas, where geomorphological and atmospheric circumstances enable continuous dust emissions. A clear latitudinal gradient in dust activity was observed, with maximum aerosol optical thickness (AOT) occurring between 17° and 20°N, mostly corresponding to the yearly movement of the Intertropical Convergence Zone (ITCZ). However, there is a notable migration of dust deposition centers northward during warm seasons (summer and autumn) and shift southward toward the southern Sahara and West Africa during cold seasons (winter and spring). The results also reveal a statistically significant long-term reduction in SDS frequency, intensity, and duration, ascribed to enhanced Sahelian vegetation, diminishing wind patterns, and changing climate oscillations. In contrast, winter exhibited an increase in SDS activity, perhaps influenced by synoptic-scale meteorological phenomena such as high-pressure anomalies. Overall, the study's methodological framework, which integrates remote sensing and spatial analytics, improves the identification and monitoring of dust sources, thereby can contribute to improving models about radiative forcing, air quality, and transboundary dust movement. Policy implications necessitate the implementation of land management methods to mitigate dust emissions, in conjunction with early warning systems for health and climate adaptation.